Hydration Status and Self-Esteem as Predictors of Athlete Burnout: A Cross-Sectional Study - William, Erwin A.; Bulut, Sefa; Rostami, Mehdi; Boltivets, Sergii; Hajji, Jamel; Yang, Jiantang; McDonnell, Maura; Chikwe, Chidinma (International Journal of Sport Studies for Health, 2024)
Objective: This study aims to explore the relationship between athlete burnout, hydration status, and self-esteem. It hypothesizes that both hydration status and self-esteem significantly predict athlete burnout. Methods and Materials: The study employed a cross-sectional design involving 230 athletes from various sports clubs and institutions. Participants were actively engaged in competitive sports for at least one year, aged between 18 and 35 years, and free from chronic health conditions. Athlete burnout was measured using the Athlete Burnout Questionnaire (ABQ), hydration status was assessed using the Urine Specific Gravity (USG) test, and self-esteem was evaluated using the Rosenberg Self-Esteem Scale (RSES). Data analysis involved Pearson correlation coefficients to assess relationships and multiple linear regression to evaluate predictive values. Results: Descriptive statistics indicated a mean score for athlete burnout of 3.10 (SD = 0.65), a mean USG for hydration status of 1.025 (SD = 0.004), and a mean score for self-esteem of 21.85 (SD = 4.72). Correlation analysis showed a positive correlation between athlete burnout and hydration status (r = 0.32, p < .001), a negative correlation between athlete burnout and self-esteem (r = -0.45, p < .001), and a weak negative correlation between hydration status and self-esteem (r = -0.15, p = .021). Regression analysis revealed that hydration status and self-esteem together explained 29% of the variance in athlete burnout, with both being significant predictors. Conclusion: The findings suggest that higher levels of dehydration and lower self-esteem are associated with increased athlete burnout. Ensuring adequate hydration and fostering self-esteem are crucial for reducing burnout. Interventions should focus on maintaining hydration, enhancing self-esteem, and promoting self-determined motivation.